EP380 Clinical outcomes and predictive factors for bladder or rectal invasive cervical cancer after definitive radiotherapy. (1st November 2019) - Park, S; Kim, YS
Abstract : Introduction/Background: This study aims to investigate the clinical outcomes in cervical cancer patients with bladder invasion following definitive concurrent chemoradiotherapy (CCRT) ± brachytherapy. Methodology: Between January 1999 and December 2015, we reviewed our clinical records of 782 women treated with definitive CCRT for cervical cancer. 57 cervical patients with FIGO stage IVA were identified. We retrospectively analyzed clinical outcomes in 57 patients with bladder or rectal invasion who underwent definitive CCRT ± brachytherapy. Results: Median follow-up duration was 38.9 months (1–190 months). Five-year cause-specific survival (CSS), disease-free survival (DFS) and local control rates (LCR) were 60.8%, 59.9% and 69.8%, respectively. The median age was 57.0 years (range, 26–81 years). Sixteen (26.7%) had para-aortic nodal involvement at the time of diagnosis. Twenty - seven of the patients (47.4%) received brachytherapy and the remaining patients received external beam radiation therapy (EBRT) boost. In multivariate analysis, para-aortic nodes involvement was associated with poorer CSS and LCR ( p <0.005). Especially, brachytherapy significantly increased LCR ( p =0.003) on multivariate analysis. After treatment, 6 patients (10.5%) had vesicovaginal fistula (VVF) and 4 patients (7%) had rectovaginal fistula (RVF). Acute hematologic toxicity of grade ≥3 was 17.5% and acute genitourinary (GU)/ gastrointestinal (GI) toxicity was 1.8%, respectively. Late GU/ GI toxicity of grade ≥3 was 14.1% and 7.0%, respectively. Conclusion: A definitive CCRT followed by intracavitary brachytherapy is feasible option for cervix cancer with bladder or rectal invasion. Adding brachytherapy was a significant factor for local tumor control with acceptable toxicity rates. Disclosure: Nothing to disclose.